Improving Ill-Structured Problem Solving Skills: Design Strategies for an Online Learning Environment - Seonyoung Jang(장선영) (인문사회과학연구, 2023)
· Research topics: This study aimed to investigate and validate design strategies for ill-structured problem solving in an online environment and to identify the potential impacts and usability of embedded supports in an online environment. · Research background: Students can enhance their problem-solving skills by solving ill-structured problems. The online learning environment is a useful environments for students to address ill-structured problems. · Differences from prior research: This study is meaningful in that design strategies to support students’ problem solving in an online learning environment was provided with the online instruction as an good example. · Research method: In Part 1, design strategies incorporating problem-solving supports were developed and validated. In Part 2, additional design strategies were developed further and validated. In Part 3, student perceptions of the effectiveness of the supports in the online instruction were investigated. · Research results: Through a review of relevant literature and the development of an online learning environment, 18 design strategies were developed. · Contribution points and expected effects: The study provides some valuable insights about developing of design strategies and elaborating on design strategies for online learning environments through development and implementation online problem solving. KCI Citation Count: 0